Legal Policy in the Regulations for the Sale of State Houses Class III (Idle State Property) Without Auction to Occupants/State Servants Reviewed From the Perspective of “The Theory of Justice” From John Rawls - Herman CS Sudira; Suhariningsih; Moh. Fadli; Iwan Permadi (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Auctions are universally believed to be the most accountable and fair trading system. This is also recognized by the Republic of Indonesia in administering the state treasury and the Management of State Property, where all sales of State Property must be carried out through auctions. The problem is, there is a legal Politics (legal policy) of differential treatment ("discrimination") for residents/civil servants in the regulation that the sale of Class III State Houses (Idle State Property) is carried out without having to go through an auction and even with a price of 50% of the fair market price assessment. . The difference in treatment raises legal (juridical) issues. The juridical problem that arises is the existence of a conflict of norms between what should be (das sollen) in the constitution contrary to the norms written in the laws and regulations (das sein). Between Article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia which states "all citizens have the same status in law and government............." is contrary to statutory regulations which is below that relates to the sale of State Houses to occupants/civil servants without an auction. From the juridical problems mentioned above, the "question" is: how is the legal politics that provides differential treatment to residents/public servants seen from the perspective of the philosophy of social justice that is in line with the goals of the Indonesian nation, namely realizing Social Justice for All Indonesian People? From the results of the analysis carried out using the evaluative-deductive analysis method, the results of the research are that legal politics that apply differential treatment of occupants/civil servants in the arrangement of selling Class III State Houses (Idle State Property) without auction are not in accordance with the meaning of "Justice of Fairness" as meant by John Rawls